2012
DOI: 10.1007/s13213-012-0520-x
|View full text |Cite
|
Sign up to set email alerts
|

Quick identification and quantification of Proteus mirabilis by polymerase chain reaction (PCR) assays

Abstract: Proteus mirabilis is an opportunistic pathogen that can cause urinary tract infection in human beings. The accurate and rapid identification and quantification of P. mirabilis is necessary for early treatment. In this study, a pair of specific primers according to the conserved ureR sequence of P. mirabilis was designed and novel systems which consisted of a polymerase chain reaction (PCR) and a real-time PCR to identify and quantify P. mirabilis were developed. For the qualitative identification by ordinary P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 35 publications
0
18
3
Order By: Relevance
“…In this study, 90.91% of the isolates were positive for ureC. However, its prevalence was relatively low when compared to the results of an earlier study [30]. Our findings revealed that testing only ureC increased the likelihood of obtaining P. mirabilis negative results.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…In this study, 90.91% of the isolates were positive for ureC. However, its prevalence was relatively low when compared to the results of an earlier study [30]. Our findings revealed that testing only ureC increased the likelihood of obtaining P. mirabilis negative results.…”
Section: Discussioncontrasting
confidence: 63%
“…As a target gene, ureC, was used to positively identify P. mirabilis as described previously [30]. Ali et al.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, 90.91% of the isolates were positive for ureC. However, its prevalence was relatively low when compared to the results of an earlier study [30]. Our results revealed that only testing ureC geneto prove that P. mirabilis may be get negative results.…”
Section: Discussioncontrasting
confidence: 59%
“…As a target gene, ureC, was used to positively identify P. mirabilis as described previously [30]. Ali et al reported that 96.66% of human P. mirabilis isolates (n = 30) recovered from the urinary tract expressed ureC [29].…”
Section: Discussionmentioning
confidence: 99%
“…To quantitatively determine the co-culture composition of the Proteus mirabilis and Providencia rettgeri biofilm community we developed a qPCR assay using primers specific for unique single-copy genes in each respective genome for P. mirabilis (5’-GGTGAGATTTGTATTAATGG and 5’-ATCAGGAAGATGACGAG, annealing temperature 58°C) and P. rettgeri (5’-AACTCGGTCAGTTCCAAACG and 5’-CTGCATTGTTCGCTTCTCAC, annealing temperature 66°C). Proteus primers were designed for the ureR gene using a previously reported forward primer [123] and a new reverse primer. Providencia primers were designed based on a phage gene only found within the Providencia genomes.…”
Section: Methodsmentioning
confidence: 99%